2020
DOI: 10.3390/app10072262
|View full text |Cite
|
Sign up to set email alerts
|

Smart Helmet and Insole Sensors for Near Fall Incidence Recognition during Descent of Stairs

Abstract: Stair falls on construction sites are leading causes of fatal injuries, and the dangers for workers are greater because they usually carry heavy loads. Nevertheless, there are very few studies related to stair falls among construction workers. The purpose of this study was to detect near fall incidence during stair descent and analyze the changes in weight bearing and center of pressure. A total of 10 healthy males participated in this study. Three experimental conditions were set up to analyze stair falls: na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Of the types of wearable sensors, sensors that can be attached or linked to the worker are the most prevalent in work settings today. Designed with “wear‐and‐forget” functionality, 36,51 attached wearables can be worn on or over clothing such as vests 52 ; attached to safety helmets 53,54 ; incorporated into footwear 55 ; worn as smart eyeglasses 33 or contact lenses 34 ; or placed in the external auditory canal 35 . Optimizing the location of attached wearables depends on the sensor's monitoring purpose, need for interaction between the sensor controls and the worker, display reachability, weight, and worker acceptance 51…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…Of the types of wearable sensors, sensors that can be attached or linked to the worker are the most prevalent in work settings today. Designed with “wear‐and‐forget” functionality, 36,51 attached wearables can be worn on or over clothing such as vests 52 ; attached to safety helmets 53,54 ; incorporated into footwear 55 ; worn as smart eyeglasses 33 or contact lenses 34 ; or placed in the external auditory canal 35 . Optimizing the location of attached wearables depends on the sensor's monitoring purpose, need for interaction between the sensor controls and the worker, display reachability, weight, and worker acceptance 51…”
Section: Wearable Sensorsmentioning
confidence: 99%
“…A total of 22 academic papers that deal with the applications of smart helmets for workers were published during the past 11 years [8,9,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] and are summarized in Table 3. The application fields include mining, construction, petrochemistry, disaster prevention, and medical treatment.…”
Section: Application Fields Of Smart Helmet Researchmentioning
confidence: 99%
“…Three studies have been reported in the construction industry, where smart helmets were primarily used to detect workplace hazards and provide risk alarms to construction workers [8,100,101]. For example, a safety helmet with gravity and head movement sensors was used at the construction site to detect a falling worker and activate emergency rescue requests [8]. Four studies on smart helmets were conducted to support voice communication between workers and warn them by detecting injuries in general manufacturing sites [102][103][104][105].…”
Section: Application Fields Of Smart Helmet Researchmentioning
confidence: 99%
See 2 more Smart Citations